Human resource management practices and employees’ job satisfaction in public hospitals in Erbil City - Hoshiar Yassin Mohamad; Abubakir Majeed Saleh (Advanced Medical Journal)
Background and objectives: Employees’ jobs satisfaction is the term most widely used and researched in field of management and organization behavior. This study aimed to explore the influence of human resource management practices on employees’ job satisfaction in public hospitals in Erbil city.